2019
DOI: 10.4028/www.scientific.net/msf.968.20
|View full text |Cite
|
Sign up to set email alerts
|

Search for Ranking Approaches of Expanded Clay Concrete Quality Criteria

Abstract: The article is devoted to ranking of quality criteria for multiparameter, multicriteria production technology of lightweight concrete depending on their significancy using fractal formalism. The proposed approach allows to determine the operation area of stability of the physicomechanical properties of expanded clay concrete with preset technology parameters depending on the size of their self-similarity area and to control the technological process relative to the determine parameter - watertightness. For con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…The formation of phases of the С 4 АН 19 type contributes to the rapid growth of the early strength of cement paste with alkaline-aluminate accelerator Na[Al(OH) 4 ]. This is consistent with the results reported in [8,10], where it is shown that in an aqueous solution NaOH increases the solubility of CaSO 4 and reduces the solubility of Ca(OH) 2 while Al(OH) 4has a delayed reaction with CaSO 4 to form ettringite. This increases the pH of the aqueous solution to about 13.8 due to an increase in the concentration of Na + in the liquid phase of Portland cement paste.…”
Section: Discussion Of Results Of Investigating the Effect Of Layered...supporting
confidence: 93%
See 1 more Smart Citation
“…The formation of phases of the С 4 АН 19 type contributes to the rapid growth of the early strength of cement paste with alkaline-aluminate accelerator Na[Al(OH) 4 ]. This is consistent with the results reported in [8,10], where it is shown that in an aqueous solution NaOH increases the solubility of CaSO 4 and reduces the solubility of Ca(OH) 2 while Al(OH) 4has a delayed reaction with CaSO 4 to form ettringite. This increases the pH of the aqueous solution to about 13.8 due to an increase in the concentration of Na + in the liquid phase of Portland cement paste.…”
Section: Discussion Of Results Of Investigating the Effect Of Layered...supporting
confidence: 93%
“…Therefore, there is an acute issue to restore building structures using special repair mixtures. At the same time, the main criteria are the high speed of repair and restoration work, as well as the durability and operational reliability of buildings and structures [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, increasing of W/C in this case plays a double role. On the one hand, the content of free water increases, which affects the porosity of hardened concrete, on the other hand, the conditions of hardening of the material and the adhesion of the cement-sand matrix to the aggregate improve [22].…”
Section: Research Resultsmentioning
confidence: 99%
“…фрактального аналізу [22][23][24][25]; мультифрактального аналізу [26][27][28] [35; 36]. Коефіцієнти парної кореляції в рівняннях прогнозу показників твердості робочої зони бочок листопрокатних валків становлять для аустенітної матриці R 2 = 0,71 та R 2 = 0,85, для карбідів хрому  R 2 = 0,95 і R 2 = 0,89.…”
Section: актуальність роботиunclassified